PENETRATION TEST OF CAFFEINE IN ETHOSOME AND DESMOSOME GEL USING AN IN VITRO METHOD - Iskandarsyah, Iskandarsyah; Puteri, Alvina Wijaya; Ernysagita, Ernysagita (International Journal of Applied Pharmaceutics, 2017)
Objectives: Caffeine has many functions including its use in the field of cosmetics. Nonetheless, the percutaneous absorption of caffeine is very low (9%), and the penetration of a substance such as caffeine in the skin is not desirable. Ethosomes and desmosomes are lipid vesicles created by the modification of liposomes containing phospholipids and ethanol or dimethyl sulfoxide (DMSO) as the penetration enhancer. The purpose of this study was to compare the effectiveness of ethosomes and desmosomes as vesicles in increasing the penetration of caffeine. Methods: Ethosomes and desmosomes were prepared using phosphatidylcholine, ethanol/DMSO, and caffeine. Phosphatidylcholine was used in the form of phospholipon 90 g that was obtained from soybeans. Observations were done including the characteristic of ethosomes and desmosomes, organoleptic observation, homogeneity observation, and in vitro penetration test using Franz diffusion cell method. Results: The cumulative penetration of caffeine ethosome gel is 3316.46±218.51 μg/cm2, with flux 249.45±30.06 μg·cm−2·hr−1, and 62.35±4.52%. The cumulative penetration of the desmosome gel is 2954.95±222.87 μg/cm2 with flux 381.68±34.91 μg·cm−2·hr−1 and 53.4±3.65%. Conclusions: It can be concluded that ethosome is more effective than desmosome in increasing the penetration of caffeine.